Employment trends in Norway - Nicolai Ellingsen; Luca Fosso; Sigurd Mølster Galaasen (Norges Bank, 2024)
This paper outlines the recently developed method for assessing the trend level in employment rates adopted by Norges Bank. The approach employs a Bayesian VAR to decompose disaggregated employment data into trend and cyclical components, using quarterly labor market data on 30 demographic sub-groups. Applied to the time period 1984-2019, we show that the estimated trend picks up known historical factors contributing to slow-moving employment dynamics. Additionally, the cyclical employment component shows strong correlation with the output gap estimate for Norway.
hdl:11250/3170067
Keywords: 330; Erwerbstätigkeit; Dekompositionsverfahren; VAR-Modell; Norwegen